ImmuneQuest: Assessment of a Video Game as a Supplement to an Undergraduate Immunology Course - Stacey L. Raimondi (Journal of Microbiology & Biology Education, 2016)
The study of immunology, particularly in this day and age, is an integral aspect of the training of future biologists, especially health professionals. Unfortunately, many students lose interest in or lack true comprehension of immunology due to the jargon of the field, preventing them from gaining a true conceptual understanding that is essential to all biological learning. To that end, a new video game, ImmuneQuest, has been developed that allows undergraduate students to “be” cells in the immune system, finding and attacking pathogens, while answering questions to earn additional abilities. The ultimate goal of ImmuneQuest is to allow students to understand how the major cells in the immune system work together to fight disease, rather than focusing on them as separate entities as is more commonly done in lecture material. This work provides the first assessment of ImmuneQuest in an upper-level immunology course. Students had significant gains in learning of information presented in ImmuneQuest compared with information discussed in lecture only. Furthermore, while students found the game “frustrating” at times, they agreed that the game aided their learning and recommended it for future courses. Taken together, these results suggest that ImmuneQuest appears to be a useful tool to supplement lecture material and increase student learning and comprehension.